Implementasi Strategi Pengembangan Interpersonal dan Intrapersonal Intelligence Siswa melalui Pembelajaran Akidah Akhlak di Kelas XI MA Ma’arif NU Pituruh Purworejo - Nuryanti Nuryanti; Abdul Majid; Nur Farida (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to describe and analyze the implementation of the strategy for developing students' interpersonal and intrapersonal intelligence through learning moral beliefs in class XI MA Ma'arif NU Pituruh Purworejo, the main objective is to focus on 3 topics, including: 1. the concept of interpersonal and intrapersonal intelligence development strategies in learning moral beliefs, 2. strategies for the application of students' interpersonal and intrapersonal intelligence development through learning moral beliefs in class XI, 3. supporting and inhibiting factors for the implementation of the strategy. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations, and documentation. The results showed that interpersonal and intrapersonal intelligence development strategies were applied through participatory learning and reflection such as group discussions, role-play, reflection journal writing, and case studies. Supporting factors for the implementation of the strategy include teacher commitment, madrasah policy support, and a positive learning environment. Meanwhile, the inhibiting factors include limited learning time, infrastructure, and emotional readiness of students. Overall, these strategies contribute to the formation of students' character and the improvement of social skills and self-reflection.